Study of International Regulatory Co-operation (IRC) arrangements for air quality The cases of the Convention on Long-Range Transboundary Air Pollution, the Canada-United States Air Quality Agreement, and co-operation in North East Asia - Kauffmann, Céline (OECD Publishing, 2020)
China, Japan and Korea have deployed a multiplicity of co-operation efforts at different levels of government to promote air quality and curb transboundary pollution. This paper identifies the existing arrangements for air quality co-operation in North East Asia and provides guidance to advance the co-operation required to face cross-border air pollution building on the experience of two long-standing co-operative agreements in this area: the Canada-United States Air Quality Agreement and UNECE's Convention on Long-Range Transboundary Air Pollution. This paper finds that the multilateral arrangements existent in North East Asia are yet to produce a comprehensive science-based regional approach to address transboundary air pollution. Key suggestions for countries to capitalise on the stronger momentum for co-operation in this area include: i) building on the existing frameworks for international regulatory co-operation for air quality; ii) advancing a common understanding of transboundary air pollution across scientific regional arrangements; and iii) strengthening the domestic policy frameworks for air quality in each country as a key prerequisite
Keywords: Environment; Governance; Canada; United States